Students Errors in Writing Procedure Text - Nur Jam’ah Hasibuan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the type errors and dominant errors of students’ writing procedure text made by the eighth-grade students of Junior High School Roudatul Islamiyah, Kota Pinang District, South Labuhanbatu Regency. This study was conducted by qualitative descriptive. The participants of this study were sixty students of the eighth grade of Junior High School Roudatul Islamiyah, Kota Pinang District, South Labuhanbatu Regency. It is VIII-1 and VIII-2 which consist of sixty students. Procedure text has the purpose to tell someone what to do or how to do something. Writing procedure text is also a process. It is not easy to write procedure text, especially in tell someone or how to do something, it is needing imagination and many vocabularies to write a procedure. There is some language feature that students usually feel hard to write, most of the students make mistake in writing procedure text. The types of errors found in students writing procedure text were omission, addition, wrong selection, and miss ordering. The errors of omission are characterized by absence of an item that must appear in a well-found utterance. The errors of addition are where some element is present which should not. The errors of wrong selection are the wrong item has been chosen in place of the right one. The errors of miss ordering are the elements presented are correct but wrongly sequenced. From result of this study the dominant errors made by students are omission, the number of highest errors is (45.2%) with the total of errors is 100. The second error is addition which the percentage of error is (25.8%) with the total of errors is 57. The third error is wrong selection which percentage (19.9%) with the total of errors is 44.  The lowest error is miss ordering which percentage (9.1%) with the total of the error is 20.